Optimizing RNAi-Target by Nicotiana benthamiana-Soybean Mosaic Virus System Drives Broad Resistance to Soybean Mosaic Virus in Soybean - Jiang, Hua; Li, Kai; Gai, Junyi (Frontiers in Plant Science, 2021)
Soybean mosaic virus (SMV) is a prevalent pathogen of soybean (Glycine max). Pyramiding multiple SMV-resistance genes into one individual is difficult, especially pathogen mutation often breaking the host-resistance, while targeting viral genome via host-induced gene silencing (HIGS) is potential to explore broad-spectrum resistance (BSR) to SMV. We identified five conserved target fragments (CTFs) S1~S5 using multiple sequence alignment of 30 SMV genome sequences and assembled the corresponding target-inverted-repeat constructs (TIRs) S1-TIR~S5-TIR. Since the inefficiency of soybean genetic transformation hinders function verification of batch TIRs in SMV-resistance, the benthamiana−chimeric-SMV and benthamiana−pSMV-GUS pathosystems combined with Agrobacterium-mediated transient expression assay were invented and used to test these TIRs’ efficacy. From that, S1-TIR assembled from 462 bp CTF-S1 with 92 % conservation rate performed the best on inhibiting SMV-multiplication. Accordingly, S1-TIR was transformed in SMV-susceptible soybean NN1138-2, then resistant-healthy transgenic T1-plants were picked out via detached-leaf inoculation assay with the stock-plants continued for progeny reproduction (T1 dual-utilization). All the four T3 transgenic progenies showed immunity to all the inoculated 11 SMV strains under individual or mixed inoculation, achieving a strong BSR. Thus, optimizing target for HIGS via transient benthamiana−chimeric-SMV and benthamiana−pSMV-GUS assays is crucial to drive robust resistance to Soybean mosaic virus in soybean and the transgenic S1-TIR-lines will be a potential breeding source for SMV control in field.